Bulgaria Housing Sector Assessment - World Bank (Washington, DC, 2017)
Bulgaria's housing sector provides a window into the broader issues of the country's social, and economic transformation. This process has been difficult, and, as was the case in many transition countries, one of the main problem areas has been the housing sector. While the government has played an active role in reforming the housing sector since 2004, and continued with initiatives to improve energy efficiency in residential buildings, new sectoral problems have emerged. Vacancy rates are extremely high, affordability concerns have intensified, and household mobility is one of the lowest among transition countries. As a result, the government is about to embark on a housing strategy, one that seeks to address the emerging issues with a particular emphasis on how this sector's functioning interacts with and affects the broader economy. This rapid assessment of Bulgaria's housing sector attempts to inform the country's forthcoming strategy. It brings together information on how the sector has performed, and relies upon the international experience, and particularly the experience of other transition economies, to set the stage for the prospective Strategy's deeper probe. Bulgaria followed a Soviet style planning approach that created one of the world's most over industrialized economies. In following this approach, it expanded many cities to service what are now bankrupt heavy industries. The result is that today the employment prospects in many locations remain dim, particularly where state-owned factories of the old regime have closed. This has resulted in massive population shifts, with some villages and towns facing complete abandonment. The country has a large ageing population, and is also experiencing one of the world's sharpest reductions in population. Population has declined by almost 20 percent since 1989, and this trend is likely to intensify over the next two decades.